Eksperimentasi Model Pembelajaran Think Pair and Share (TPS) dengan Pendekatan Saintifik pada Materi Fungsi Ditinjau dari Interaksi Sosial Siswa - Cahyono, Heri (AlphaMath : Journal of Mathematics Education, 2020)
The purpose of this study is to find out which gives better mathematics learning achievement in the TPS type cooperative learning model with a scientific approach, students with high, medium, or low levels of social interaction on the subject matter of function. This research is a quasi-experimental study. The population is all eighth grade students of state junior high schools in Ngawi Regency 2016/2017 school year. The sampling technique uses stratified cluster random sampling, so that students are obtained at SMP Ngrambe 3, SMP Negeri 2 Paron, and SMP Negeri 2 Widodaren as a research sample of 90 students. Data collection instruments used achievement tests and student social interaction questionnaires. Hypothesis testing using analysis of variance (anava) one cell path is not the same. The conclusion of this study is the type of TPS cooperative learning model with a scientific approach to students with high levels of social interaction provides better mathematics learning achievement compared to students with moderate and low levels of social interaction, and mathematics learning achievement of students with moderate levels of social interaction as well compared to students with levels of interaction socially low in providing mathematics learning achievement on the subject matter of function.